Cognition in Rapid Eye Movement Sleep Behavior Disorder - Gagnon, Jean-François; Bertrand, Josie-Anne; Génier Marchand, Daphné (Frontiers in Neurology, 2012)
Rapid eye movement (REM) sleep behavior disorder (RBD) is a parasomnia characterized by excessive muscle activity and undesirable motor events during REM sleep. RBD occurs in approximately 0.5% of the general population, with a higher prevalence in older men. RBD is a frequent feature of dementia with Lewy bodies (DLB), but is only rarely reported in Alzheimer’s disease. RBD is also a risk factor for α-synuclein-related diseases, such as DLB, Parkinson’s disease (PD), and multiple system atrophy. Therefore, RBD has major implications for the diagnosis and treatment of neurodegenerative disorders and for understanding neurodegeneration mechanisms. Several markers of neurodegeneration have been identified in RBD, including cognitive impairments such as deficits in attention, executive functions, learning capacities, and visuospatial abilities. Approximately 50% of RBD patients present mild cognitive impairment (MCI). Moreover, RBD is also associated with cognitive decline in PD.